2017
DOI: 10.3389/fphar.2017.00352
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effects of Ursolic Acid against Gamma Irradiation-Induced Damage Are Mediated through the Modulation of Diverse Inflammatory Mediators

Abstract: This study was aimed to evaluate the possible protective effects of ursolic acid (UA) against gamma radiation induced damage both in vitro as well as in vivo. It was observed that the exposure to gamma radiation dose- and time-dependently caused a significant decrease in the cell viability, while the treatment of UA attenuated this cytotoxicity. The production of free radicals including reactive oxygen species (ROS) and NO increased significantly post-irradiation and further induced lipid peroxidation and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…It is well known today that oxidative and nitrosative stresses are potent pathogenic mechanisms contributing to gamma radiation-induced damage. Recent studies have proposed that gamma radiation significantly increased intracellular ROS and reactive nitrogen species formation [1,62]. Our results demonstrated that gamma irradiation with 20 Gy significantly decreased cell viability in keratinocytes, accompanied by increased ROS production and NO release and decreased GSH levels.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…It is well known today that oxidative and nitrosative stresses are potent pathogenic mechanisms contributing to gamma radiation-induced damage. Recent studies have proposed that gamma radiation significantly increased intracellular ROS and reactive nitrogen species formation [1,62]. Our results demonstrated that gamma irradiation with 20 Gy significantly decreased cell viability in keratinocytes, accompanied by increased ROS production and NO release and decreased GSH levels.…”
Section: Discussionsupporting
confidence: 61%
“…The regulation of the NF-κB pathway is involved in the survival and death of cells exposed to gamma radiation [48]. Our previous study indicated that gamma radiation exposure timeand dose-dependently enhanced NF-κB DNA binding activities in HaCaT cells [62], while celastrol treatment was found to suppress this increase. Our observations were in agreement with a recent study [48].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations